Overview of solutions in quantum information technologies, part 1 - Białek, Kalina; Brz´osko, Alicja E.; Małecki, Piotr A.; Łubian, Grzegorz; Rowicki, Krzysztof; Strzałkowski, Jacek Strzałkowski; Leczycki, Borys; Romaniuk, Ryszard S. (International Journal of Electronics and Telecommunications, 2026)
The article presents an overview of the quantum technologies across diverse domains. The exploitation of quantum phenomena—such as superposition, entanglement, and quantum interference—allows the introduction of practical and sometimes still theoretical innovations in a wide range of technologies that at some point met an insuperable obstacle in their development. The first part of the series of articles focuses on the influence of quantum information technologies on cryptography, computational physics, hardware, digital electronics, machine learning and healthcare applications. The seven sub-articles address both the opportunities and challenges of deploying quantum technologies.